Pengaruh Penggunaan Media Sedotan Terhadap Hasil Belajar Perkalian Matematika Siswa Kelas III A di SD Negeri 3 Rajabasa Kota Bandar Lampung - Pitaloka, Yulia; Mashari , Ali; Soraya , Rahayu (JURNAL ILMU PENDIDIKAN, 2023)
The relationship between the straw learning media and the learning outcomes of math multiplication for class III A students at SD Negeri 3 Rajabasa Bandar Lampung City. This study aims to describe whether there is an impact of straw learning media on the learning outcomes of mathematic calculations for class III A students at SD Negeri 3 Rajabasa Bandar Lampung City. The results of the researcher’s survey found that the results of students multiplication learning were still low. The method used in this study was quantitative with a pre-experimental method in the from of a one group pretest-posttest desigen. The population in this study were third grade students at SD Negeri 3 Rajabasa. The sample of this research is 20 students. The sampling technique used purposive sampling technique, using tests, documentation, data analysis techniques and using the t-test. The results of the study are shown by the results of the t-tes (paired sample 1 test) for the same sample with diffrent treatment (pretest-postest) by producing a t count of 11.427 and a table of 1,725. Which proves that there is an influence of straw learning media on results learn math multiplication.